El maravilloso regreso de Jacob Cerf - Miller, Rebecca, 1962-; Ministral, Clara; Miller, Rebecca, 1962- (Madrid : Siruela, 2014)
An eighteenth-century Jewish peddler is reincarnated as a fly in present-day Long Island, and becomes involved in the lives of two residents.
Online resource; title from ePub title page (Digitalia, viewed April 8, 2016)
Keywords: Peddlers -- Fiction; Reincarnation -- Fiction; Long Island (N.Y.) -- Fiction; Electronic books